If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 5y = 4 Solving 10 + 5y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5y = 4 + -10 Combine like terms: 10 + -10 = 0 0 + 5y = 4 + -10 5y = 4 + -10 Combine like terms: 4 + -10 = -6 5y = -6 Divide each side by '5'. y = -1.2 Simplifying y = -1.2
| 7(1/2)*x=7/8 | | 7(1/2)^x=7/8 | | 8x-15=5x-12 | | -x-2=-4x+7 | | q+2=6q | | 6q+0(1-q)= | | 2(3a+6)=4(3-7a)+6a | | f(x)=5e^2x-e | | 3q+2(1-q)= | | 6x+16=10x+44 | | 1.6(x-3)=-80 | | .6*x+4=7 | | 4x-13-6x+4=3-9X-7+3x | | 8x-2=4y | | A=p+petfory | | x+(2x+1)=-2 | | 0.4t-0.3=1.8-0.1(2t+9) | | 4x^3-2x^2+3=0 | | 3(y-3)-2=7 | | 2x+2y=81 | | 2n/4n | | 4(a-3)=6a+11 | | 4a-3=6a+11 | | (4a-3)+(6a+11)= | | cos9x/9x | | x^2+y^2+6z^2=81 | | (x+5)(x-5)(x+1)(x-6)= | | 8n-3=4n+17 | | X^2-3x-x+3=0 | | 4a-3=6 | | 5*x+2=6x+3 | | 5y+10(y+14)+25(y+13)=905 |